Hodnocení finanční situace vybrané soukromoprávní korporace metodami finanční analýzy a návrhy na její zlepšení - Luzarová, Aneta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Bakalářská práce na téma Hodnocení finanční situace soukromoprávní korporace metodami finanční analýzy a návrhy na její zlepšení si klade za cíl analyzovat a zhodnotit společnost Teva Czech Industries s.r.o. a následně navrhnout doporučení na zlepšení finanční situace. První část je věnována teoretickým pojmům, týkající se finanční analýzy. Praktická část obsahuje samotnou analýzu společnosti včetně výpočtu vybraných ukazatelů. Na závěr jsou navržena opatření vedoucí ke zlepšení finanční situace podniku.

The bachelor's thesis on the topic Evaluation of the Financial Situation of a Private Corporation by Methods of Financial Analysis and Suggestions for its Improvement aims to analyze and evaluate the company Teva Czech Industries s.r.o. and then make recommendations to improve the financial situation. The first part is devoted to theoretical concepts related to financial analysis. The practical part contains the analysis of the company itself, including the calculation of selected indicators. Finally, measures are proposed to improve the financial situation of the company.
Evaluation of the Economic Situation of the Selected Private Corporation and Proposals to its Improvement
Keywords: finanční analýzy; rozvaha; výkaz zisku a ztrát; výroční zpráva; finanční ukazatele; rentabilita; likvidita; financial analysis; balance sheet; profit and loss account; annual reports; financial indicators; profitability; liquidit